Spatial distribution of Chikungunya cases in the state of Piauí - Brazil (2015-2019) - Matheus Henrique da Silva Lemos; Lauro Lourival Lopes Filho; Maria Amélia de Oliveira Costa; Dinah Alencar Melo Araújo; Ticianne da Cunha Soares; Filipe Melo da Silva; Raydelane Grailea Silva Pinto; Vicente de Paula Sousa Júnior (Universidade Estadual de Maringá, 2023)
This study aimed to analyze the spatial distribution of chikungunya cases in Piauí between 2015 and 2019. This was a spatial ecological study of notified and confirmed cases of chikungunya, with data from the Notifiable Diseases Information System (SINAN) from 2015 to 2019. The X² association test was applied for the bivariate analysis and the spatial analysis was performed from the data treatment to combine with the cartographic base in the free software Qgis (version 3.16.7 Hannover). During this period, 9596 cases and 7950 confirmed cases of chikungunya were reported.  The city of Teresina (53.21%) and the health region Entre Rios (58.27%) had the highest records. Females (58.40%), aged between 20 and 34 years (29.63%) and mixed race (50.26%) were the most affected. Regarding education, 56.55% were ignored and, regarding the months of notification, the months of the 1st semester had the highest number of cases (62.8%). Chikungunya cases are concentrated in poles with large population flows. In this way, the identification of the epidemiological profile, as well as its main risk factors, is a way of helping the health system of the entire state in the elaboration of specific control policies for the population most vulnerable to the disease.